On Some Sequence Spaces of Bicomplex Numbers - Parajuli, Purushottam; Pahari, Narayan Prasad; Ghimire, Jhavi Lal; Jaiswal, Molhu Prasad (Nepal Journal of Mathematical Sciences, 2025)
In 1892, Segre introduced the concept of bi-complex numbers. The main contribution in bicomplex analysis was the pioneering works in Functional analysis. It is a new subject, not only relevant from a mathematical point of view, but also has significant applications in physics and engineering. This article provides an overview of bi-complex numbers and examines the completeness of certain sequence spaces of bi-complex numbers. Additionally, the study explores their algebraic, topological, and geometric properties, contributing to a deeper understanding of these spaces.